Análise da avaliação de desempenho do servidor técnico-administrativo, no estágio probatório, da Universidade Federal do Espírito Santo - Andrade, Ligiane Bornela de Souza (2019)
The probationary phase is an adaptation, training and evaluation period for public servants in effective exercise, who are admitted in public service after approval by public tender. During this period, their aptitude and capacity for performing their role will be evaluated by a commission formed specifically for this task, according to the criteria assiduity, discipline, initiative, productivity and responsibility. If the public servants are approved in this phase, they acquire job stability after three years of effective exercise at the role. At the Universidade Federal do Espírito Santo (UFES) the performance evaluation of educational technical-administrative servants (TAE) in the probationary phase is regulated by the Resolution 08/2007 and altered by the Resolutions 38/2007 and 07/2014 from the University Council (Conselho Universitário). In view of this, this research has as its main objective to analyse the current performance evaluation model of UFES educational technical-administrative servants in the probationary phase. Applying Benchmarking, the research used comparative methodology, with a qualitative, descriptive and documental approach. The sample was composed by the performance evaluation processes for servants in probationary phase from the federal universities with the highest Institutional Concept (Conceito Institucional) according to the Education Ministry (Ministério da Educação e Cultura), and by the evaluation process from UFES as well. The list of federal universities with the highest Institucional Concept was obtained in the Higher Education Regulation System (eMEC) and the information related to the performance evaluation were extracted from the universities sites and from answers requested of the universities human resources managers through email messages. It was noted that the performance evaluation for educational-technical servants at the probationary phase currently in place at UFES has not been as effective a tool as it could, since it presents weaknesses and lacks some improvements in the evaluation process. Therefore, the results obtained supported the proposal of a new model for performance evaluation of educational-technical servants at the probationary phase as an applicable technical product within UFES.